Characterization of molecularly imprinted polymers for the extraction of tobacco alkaloids and their metabolites in human urine. (26th April 2022) - Mulder, Haley A.; Pearcy, Adam C.; Halquist, Matthew S.
Abstract: Molecularly imprinted polymers (MIPs) are synthetic polymers designed to selectively extract target analytes from complex matrices (including biological matrices). The literature shows that MIPs have a degree of cross‐selectivity from analytes within the same class of compounds. A commercially available MIP for tobacco‐specific nitrosamines (TSNAs) is designed to be class selective for four TSNA compounds. This study sought to characterize the extent of cross‐selectivity of the TSNA MIPs with other tobacco alkaloids. Cross‐selectivity and recovery of the SupelMIP™ TSNA SPE cartridges was assessed with N ‐nitrosonornicotine (NNN), nicotine, cotinine and morphine. Their recoveries were compared with the recoveries of a nonimprinted polymer SPE cartridge, and two traditional SPE cartridges: a Waters mixed‐mode cation exchange cartridge and a Waters hydrophilic–lipophilic balance cartridge. NNN and cotinine had the highest recoveries with the MIP cartridge, over 80%, and cotinine samples in urine had >80% recoveries. Nicotine had highly variable recoveries, possibly owing to differing chemical properties from the TSNAs. All three analytes had significantly different recoveries with the MIP cartridges compared with the traditional SPE cartridges. Morphine displayed nonspecific interactions with the MIP cartridges. Utilization of the TSNAs' cross‐selectivity allows for simultaneous extraction and identification of multiple tobacco biomarkers using one extraction technique.